Development and the changing global environment - Sinha, Rajiv K. (Jaipur, 2007)
Development and environment was a major issue of the 20 century and the debate continues in the 21 century. The economic development programs based on 'fossil fuel economy' essential to deliver a minimum quality of life to people, is also threatening their existence. Mankind is caught in a vicious circle of 'economic development vis-à-vis environmental degradation'. In the name of development, the world today produces more instruments to 'kill' rather than 'cure'; spends thousands times more resources on building of 'weapons of mass destruction' than on all economic programs for human development -- to eradicate poverty, hunger and malnutrition. Environmental degradation and economic decline (aggravating poverty) feed on each other, and the fate of the poor and the fate of the planet (Earth) have become tightly entwined. Economic deprivation and environmental degradation thwarts all efforts towards sustainable development. Although the desirability of development is universally recognized, recent years have witnessed rising concern whether the environmental degradation will limit development, thus impairing the quality of life of present and the future generations too. The book unravels some of these issues. This book will definitely serve not only as an excellent reference material but also as a practical guide for the teachers, research workers, students and environmentalists.
Keywords: Economic development